Strengthening the Values of Religious Moderation Through Al-Qur'ān Textbooks at Madrasah Ibtidāiyyah - Imronudin; Azwar Anas; Ucu Astira (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
In this context of religious moderation, textbooks must not contain elements that trigger acts of violence. Islam, as a religion, does not educate students to commit acts of violence in children's education, whether through words, behavior, or physical actions. The presence of the Al-Qur'an and Hadith in the curriculum is vital in education because they discuss the basic understanding of Islamic teachings applied in everyday life. This research uses the In Service Learning method by collaborating with partners, namely the principal of MI Al-Qolam, Kp. Dukuh Ilir RT 03/03, Dukuh village, Cibungbulang sub-district, regency. Bogor. The method for carrying out activities is the off-the-job training method with a lecture approach, namely giving lectures. This activity focuses on introducing and strengthening the values of religious moderation in the educational environment, especially in madrasah ibtidaiyyah. This activity concludes that educators feel it helped develop an analysis of the values of religious moderation through the Al-Qur'an and Hadith Textbook for Madrasah Ibtidaiyyah published by the Ministry of Religion of the Republic of Indonesia in 2020. This activity aims to increase educators' understanding and analysis in integrating the values of religious moderation in learning Al-Qur'an Hadith